A preliminary study on the distribution of Mimosa pigra in Gorongosa National Park: reasons and causes - Vieira, Márcia Bugalho, 1990- (2015)
Tese de mestrado. Biologia (Ecologia e Gestão Ambiental). Universidade de Lisboa, Faculdade de Ciências, 2015